Effect of EpCAM, CD44, CD133 and CD166 expression on patient survival in tumours of the ampulla of Vater. Issue 2 (30th November 2011) - Piscuoglio, Salvatore; Lehmann, Frank S; Zlobec, Inti; Tornillo, Luigi; Dietmaier, Wolfgang; Hartmann, Arndt; Wünsch, Peter H; Sessa, Fausto; Rümmele, Petra; Baumhoer, Daniel; Terracciano, Luigi M
Abstract : Background: Carcinomas of the Vaterian system are rare and presumably arise from pre-existing adenomas. According to the cancer stem cell (CSC) hypothesis, only a small subset of tumor cells has the ability to initiate and develop tumor growth. In colorectal cancer, CD44, CD133, CD166 and EpCAM have been proposed to represent CSC marker proteins and their expression has been shown to correlate with patient survival. Aims: To evaluate a potential role of these CSC proteins in tumors of the ampulla of Vater, we investigated their expression in 175 carcinoma, 111 adenoma and 152 normal mucosa specimens arranged in a Tissue Microarray format. Materials and methods: Membranous immunoreactivity for each protein marker was scored semi-quantitatively by evaluating the number of positive tumor cells over the total number of tumor cells. Median protein expression levels were used as cut-off scores to define protein marker positivity. Clinical data including survival time were obtained by retrospective analysis of medical records, tumor registries or direct contact. Results: The expression of all evaluated marker proteins differed significantly between normal mucosa, adenoma and carcinoma samples. In all markers, we found a tendency towards more constant expression from normal to neoplastic tissue. EpCAM expression was significantly correlated with better patient survival. The increased expression of CD44s, CD166 and CD133 from normal mucosa samples to adenoma and carcinoma was linked to tumor progression. However, there was no statistically significant correlation with survival. Conclusion: Our findings indicate, that in ampullary carcinomas, loss of expression of EpCAM may be linked to a more aggressive tumor phenotype.